Union Security Clauses Versus Freedom of Trade Union Association - Kalamatiev Todor; Ristovski Aleksandar (Faculty of Law, University of Niš, 2017)
The paper analyzes the freedom of trade union association and organization in light of the union security clauses with particular accent on their admissibility in the Macedonian labour law system and the level of their compliance/non-compliance with the Macedonian labour legislation. The union security clauses are reviewed in terms of the initiative for the establishment of a Fund for promotion of social dialogue in the Republic of Macedonia that is supposed to provide for the possibility of “obliging” the non-unionized workers to pay for an agency fee in order to be subsumed under the normative content of the concluded collective agreements. Starting from this, the paper shall refer to possible resolution of the issues regarding the interpretation of the freedom of association of workers as well as the applicability of the collective agreements. In the paper, the authors shall conduct an analysis of the “union security clauses” from the perspective of the comparative labour law and comparative legal practice of certain countries in which such clauses are regulated, as well as the countries where they are prohibited.
Keywords: union security clauses, closed shop, union shop, agency shop, freedom of trade union association.